Breast Cancer in Pregnancy: A Case Report of a Mammary Ulcer in a 37-Year-Old Woman - Putri Rahayu Muthmainnah; Erlin Syahril; Andi Irwansyah Ahmad (Journal of Community Health Provision, 2026)
Breast cancer occurring during pregnancy, or pregnancy-associated breast cancer (PABC), is a rare condition but presents complex diagnostic and therapeutic challenges. Physiological changes in the breast during pregnancy can mask early signs of malignancy, leading to delays in diagnosis and treatment. To report a case of suspected breast cancer in a pregnant patient and discuss its clinical characteristics, investigations, and management. This case report is based on the history, physical examination, laboratory tests, and ultrasound of a 37-year-old female patient, 24 weeks pregnant, who presented with a right breast lump. The patient presented with a right breast mass with ulceration measuring more than 5 cm in diameter, accompanied by enlarged axillary lymph nodes. Laboratory examinations revealed anemia and leukocytosis. Ultrasonography revealed an irregular, hypoechoic lesion with a BIRADS classification of 5, suggestive of malignancy. The working diagnosis was a right breast ulcer with suspicion of breast cancer. Early detection of breast cancer during pregnancy is crucial to prevent delayed diagnosis and improve prognosis. A multidisciplinary approach to management is essential to ensure the safety of both mother and fetus